Development of Smart Dental Impression Trays on Operator Satisfaction During Dental Impression in Healthcare Services - Islami, Muhammad Rizqi Fauzi; Ningtyas, Endah Aryati Eko; Fatmasari, Diyah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Health is the most important aspect of human life, both physically and mentally. Oral and dental health plays a crucial role in maintaining the body's functional balance. Tooth loss can disrupt chewing, nutrition, and overall quality of life. However, it can be managed with the use of dentures. One of the challenges in dental impression-taking is the gag reflex, which can be minimized by selecting the appropriate impression tray and optimizing the setting time of alginate. Innovations such as temperature sensors for real-time monitoring and music therapy can enhance accuracy and patient comfort.Method: This study employs the Research and Development (R&D) method, which involves stages of information gathering, product design, expert validation, and product testing. The research respondents consist of operators (medical personnel) who perform dental impressions. Data is analyzed using statistical tests to evaluate the effectiveness of the developed device.Result: The research results indicate that the use of Smart Dental Impression Trays significantly enhances operator satisfaction, with a mean score of 4.80 ± 0.422 compared to the control group at 3.60 ± 0.699 (p-value = 0.001).Conclusion: Smart Dental Impression Trays are effective in enhancing operator satisfaction during the dental impression procedure. This innovation has the potential to be a solution for dental healthcare services in improving the quality of dental impressions.Keywords: Smart dental impression trays, operator satisfaction, temperature sensor, relaxation music